Catechol O-methyltransferase val(158)-met genotype and individual variation in the brain response to amphetamine - Mattay, Venkata S. (The National Academy of Sciences, 2003)
Monamines subserve many critical roles in the brain, and monoaminergic drugs such as amphetamine have a long history in the treatment of neuropsychiatric disorders and also as a substance of abuse. The clinical effects of amphetamine are quite variable, from positive effects on mood and cognition in some individuals, to negative responses in others, perhaps related to individual variations in monaminergic function and monoamine system genes. We explored the effect of a functional polymorphism (val(158)-met) in the catechol O-methyltransferase gene, which has been shown to modulate prefrontal dopamine in animals and prefrontal cortical function in humans, on the modulatory actions of amphetamine on the prefrontal cortex. Amphetamine enhanced the efficiency of prefrontal cortex function assayed with functional MRI during a working memory task in subjects with the high enzyme activity val/val genotype, who presumably have relatively less prefrontal synaptic dopamine, at all levels of task difficulty. In contrast, in subjects with the low activity met/met genotype who tend to have superior baseline prefrontal function, the drug had no effect on cortical efficiency at low-to-moderate working memory load and caused deterioration at high working memory load. These data illustrate an application of functional neuroimaging in pharmacogenomics and extend basic evidence of an inverted-“U” functional-response curve to increasing dopamine signaling in the prefrontal cortex. Further, individuals with the met/met catechol O-methyltransferase genotype appear to be at increased risk for an adverse response to amphetamine.